Understanding the dynamics of prison violence: An experiential model for teaching and training - Braswell, Michael (American journal of criminal justice, 1984)
Although a number of intervention and prevention strategies have been attempted, violence in prisons continues to be a substantial problem. This paper provides an experiential case studies model for acquainting students and correctional practitioners with the realities involved in volatile prison situations. Analytical and experiential case studies methods are compared. Sample cases are included to aid student/practitioners in perceiving and resolving violence-related problems from the perspective of the different populations (e.g., inmate, administrative) found in a typical prison environment.